Implementasi Pengadaan Barang dan Jasa Pemerintah Berdasarkan Peraturan Presiden Nomor 46 Tahun 2025 ( Studi di Lingkungan Kejaksaan Cianjur) - Dhanitya Putra Prawira; Ariyanti (Postgraduate University of Merdeka Malang, 2026)
This study aims to analyze the implementation of Presidential Regulation Number 46 of 2025 as an amendment to Presidential Regulation Number 16 of 2018 concerning government procurement of goods/services at the Cianjur District Attorney's Office and to identify obstacles that arise in its law enforcement. The study uses a qualitative method with an empirical approach through in-depth interviews, observations, and documentation studies, with a theoretical basis of legal effectiveness, legality theory, criminal liability theory, and law enforcement theory. The results of the study indicate that the implementation of Presidential Regulation 46 of 2025 has been carried out formally through the establishment of Commitment Making Officers, Procurement Officers, and Selection Working Groups, as well as the utilization of the Electronic Procurement System. However, implementation has been suboptimal due to ongoing procurement delays, irregular documentation, limited resources, and minimal training related to the latest regulations. Obstacles to law enforcement include unclear boundaries between administrative and criminal errors, officials' concerns about the risk of criminalization, weak preventive oversight, and a lack of understanding of new procedures. The study concluded that the effectiveness of the Presidential Regulation's implementation remains limited to administrative compliance and has not achieved the substantive goals of efficiency, transparency, and accountability. Clearer technical guidelines, strengthened oversight, increased human resource capacity, and legal protection for officials acting in good faith are needed.